How could discourse theories of identity formation critically engage patient-centered care in older adults?. (17th September 2018) - Horton, Anna; Horton, Simon
Abstract : Purpose: The purpose of this paper is to explore how discourse theories can contribute to the concept of identity formation within a patient- or person-centered care (PCC) orientation, to enable more critical engagement with PCC in older people. Design/methodology/approach: This is a conceptual paper. Findings: This paper concludes that the discourse literature has important insights for understanding identity formation in older people as operationalized in the context of PCC in three particular ways: accounting for multiplicity in patients' identity; exploring "the devolution of responsibility" to address shifts in performing identities in clinical encounters; and attending to a "crisis of positioning" to engage empowerment discourse within a PCC philosophy. Originality/value: Whilst a notion of patient identity is at the heart of PCC, the concept remains inconsistent and underdeveloped. This is particularly problematic for the quality of care in older adults, as PCC has become increasingly synonymous with care of older people. Discourse theories of identity formation can be used to critically engage with identity within the context of PCC, so as to develop more nuanced understandings of "the person" or "the patient, " with the potential to improve research into care for aging and older adults.